2022
DOI: 10.1111/jpn.13753
|View full text |Cite
|
Sign up to set email alerts
|

Influence of refeeding on production, blood biochemistry parameters, and reproduction in underfed Kacang goat does

Abstract: This research aimed to investigate the effect of refeeding on production, blood biochemical parameters, and reproduction in underfed Kacang goat does. Twelve 2-3year-old Kacang goats scored (body condition score [BCS]: 1-1.5) with poor body condition but appeared healthy, gave normal births 3-4 months before but no longer nursing their youngs, and anestrus were used in this study. The experiment consisted of 110 days with 14 days of adaptation period and 96 days of feeding treatment and data collection. After … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 71 publications
(108 reference statements)
0
6
0
Order By: Relevance
“…Because of the high metabolic demands of maintaining basal energy reserves and milk production, reproduction activity in dairy animals is restricted. Feeding limitations or excesses have been linked to reproduction disruption [ 13 ], which has been shown to reduce the future rate of kidding. The results of this study also showed that a well-balanced diet (nutrition intake and nutrition needed to meet equilibrium scale ±5%) is essential for reproductive efficiency and that this is proven in blood and hormonal parameters.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Because of the high metabolic demands of maintaining basal energy reserves and milk production, reproduction activity in dairy animals is restricted. Feeding limitations or excesses have been linked to reproduction disruption [ 13 ], which has been shown to reduce the future rate of kidding. The results of this study also showed that a well-balanced diet (nutrition intake and nutrition needed to meet equilibrium scale ±5%) is essential for reproductive efficiency and that this is proven in blood and hormonal parameters.…”
Section: Discussionmentioning
confidence: 99%
“…This condition occurs because hemostatic ability stabilizes GLU levels as long as energy and protein needs do not exceed or fall below 35% and allows adult dairy animals to maintain normal blood GLU levels [ 17 , 18 ]. In this study, dairy goats’ GLU also ranged in normal concentrations from 2.19 to 4.5 mmol/l [ 13 ]. T1 and T2 seemed to have slightly higher GLU levels than T0 because of the increased energy intake used in gluconeogenesis at T0 [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations